Dead time determination and its influence to retention index in GC system using polar capillary column - Idroes, Rinaldi; Oesman, Frida (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
In this research for the determination of dead timeused a method that is mathematically calculated as iteration and linearization of the polar capillarry column in Gas Chromatography (GC) type DN-Wax, by injecting the homologous series of n-alkanes (n-pentane up to n-decane) on GC system. The dead time values obtained are then used to determine the Kovats Retention Index (Retention Index, RI). The results indicated that the retention index had values of systematic error those are more accurate than the retention time (tR), corrected retention time (tR') and retention factor(k'), but the retention index shows the value of random error slightly larger than with other retention parameters. In this study the average values obtained by the iteration method, the dead time was 3.52 minutes with a correlation coefficient of 0.9998.Retention index values obtained are at the confidence level 92.11%-97.06% with the systematic errors 2.04%-7.89%, while the linearization method showed the average value of the dead time 3.3 minutes witha correlation coefficient of 0.9992, but the value of retention index values obtained show that the systematic error is very large.Key words:Dead time, Retention Index, Homologous Series, GC